2009
DOI: 10.1186/1748-5908-4-83
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based practice implementation: The impact of public versus private sector organization type on organizational support, provider attitudes, and adoption of evidence-based practice

Abstract: BackgroundThe goal of this study is to extend research on evidence-based practice (EBP) implementation by examining the impact of organizational type (public versus private) and organizational support for EBP on provider attitudes toward EBP and EBP use. Both organization theory and theory of innovation uptake and individual adoption of EBP guide the approach and analyses in this study. We anticipated that private sector organizations would provide greater levels of organizational support for EBPs leading to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
155
1
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(171 citation statements)
references
References 51 publications
6
155
1
7
Order By: Relevance
“…, 학습조직 구축요인 [6]의 영향을 받는 것으로, EBP에 대한 태도는 EBP에 대한 지식/기술 [13], 신념 [14], EBP를 위한 조직문화와 준비도 [7,13]의 영향을 받는 것으로 경로를 설정하였다. 그리고 조직혁신성은 학습조직 구축요인 [15]의 영향을 받 는 것으로, EBP 실행은 EBP에 대한 지식/기술 [5], 신념 [5,6,12], 태 도 [7], EBP를 위한 조직문화와 준비도 [7,11], 학습조직 구축요인 [8], …”
unclassified
See 1 more Smart Citation
“…, 학습조직 구축요인 [6]의 영향을 받는 것으로, EBP에 대한 태도는 EBP에 대한 지식/기술 [13], 신념 [14], EBP를 위한 조직문화와 준비도 [7,13]의 영향을 받는 것으로 경로를 설정하였다. 그리고 조직혁신성은 학습조직 구축요인 [15]의 영향을 받 는 것으로, EBP 실행은 EBP에 대한 지식/기술 [5], 신념 [5,6,12], 태 도 [7], EBP를 위한 조직문화와 준비도 [7,11], 학습조직 구축요인 [8], …”
unclassified
“…그리고 조직혁신성은 학습조직 구축요인 [15]의 영향을 받 는 것으로, EBP 실행은 EBP에 대한 지식/기술 [5], 신념 [5,6,12], 태 도 [7], EBP를 위한 조직문화와 준비도 [7,11], 학습조직 구축요인 [8], …”
unclassified
“…For health, examples saw greater levels of private sector support, attitudes, and use of evidence-based practice implemented by mental health service providers in the USA (Aarons et al 2009). Similarly, Heponiemi et al (2010) reported a comparison of Finnish physicians which saw not only greater levels of positive private sector job attitudes and well-being but also organizational justice and job control than in the public sector.…”
Section: Introductionmentioning
confidence: 99%
“…Thus one of the first tasks for an implementation professional interested in optimizing the capacity for sustainable impact of a given intervention is to undertake, in collaboration with local stakeholders and experts, an analysis of the system into which the new innovation will be inserted. Stakeholder analyses and network mapping and systems mapping (Aarons, Sommerfield, & Walrath-Greene, 2009;Paina & Peters, 2012) are processes that allow a new innovation to be viewed from multiple perspectives and allow developers and providers to anticipate how the innovation will align constructively with the existing structures, how it may disturb the existing system in both beneficial and antagonistic ways, and to identify the key agencies and key individual stakeholders whose support and leadership will be critical to the innovation's success. This involves much more than developing a communications plan and requires would-be innovators to recognize themselves within a co-constructed process that reaches beyond the parameters of their own specific planned program or service.…”
Section: Key Implementation Constructs and Their Deployment As Tools mentioning
confidence: 99%